Antimicrobial Resistance Dynamics in Chilean Shigella sonnei Strains Within Two Decades: Role of Shigella Resistance Locus Pathogenicity Island and Class 1 and Class 2 Integrons - Toro, Cecilia S.; Salazar, Juan Carlos; Montero, David A.; Ugalde, Juan Antonio; Díaz, Janepsy; Cádiz, Leandro A.; Henríquez, Tania; García, Camila; Díaz, Patricia; Camponovo, Rossanna; Hermosilla, Germán; Ulloa, María Teresa (Frontiers in Microbiology, 2022)
Shigellosis is an enteric infectious disease in which antibiotic treatment is effective, shortening the duration of symptoms and reducing the excretion of the pathogen into the environment. Shigella spp. the etiologic agent, are considered emerging pathogens with a high public health impact due to the increase and global spread of multidrug-resistant (MDR) strains. Since Shigella resistance phenotype varies worldwide, we present an overview of the resistance phenotypes and associated genetic determinants present in 349 Chilean S. sonnei strains isolated during the periods 1995-1997, 2002-2004, 2008-2009, and 2010-2013. We detected a great variability in antibiotic susceptibility patterns, finding 300 (86%) MDR strains. Mobile genetic elements (MGE) such as plasmids, integrons, and genomic islands have been associated with the MDR phenotypes. The Shigella resistance locus pathogenicity island (SRL PAI), which encodes for ampicillin, streptomycin, chloramphenicol, and tetracycline resistance genes, was detected by PCR in 100% of the strains isolated in 2008-2009, but was less frequent in isolates from other periods. The presence or absence of SRL PAI was also differentiated by pulsed-field gel electrophoresis. An atypical class 1 integron harbors the blaOXA-1-aadA1-IS1 organization was detected as part of SRL PAI. The dfrA14 gene conferring trimethoprim resistance was present in 98.8% of 2008-2009 isolates, distinguishing them from the SRL-positive strains isolated before that. Thus, it seems an SRL-dfrA14 S. sonnei clone spread during the 2008-2009 period and declined thereafter. Besides, SRL-negative strains harboring class 2 integrons with or without resistance to nalidixic acid were detected from 2011 onward, suggesting the circulation of another clone. Whole-genome sequencing of selected strains confirmed the results obtained by PCR and phenotypic analysis. It is highlighted that 70.8% of the MDR strains harbored one or more of the MGE evaluated, while 15.2% lacked both SRL PAI and integrons. These results underscore the temporal dynamics of antimicrobial resistance in S. sonnei strains circulating in Chile, mainly determined by the spread of MGEs conferring MDR phenotypes. Since shigellosis is endemic in Chile, constant surveillance of antimicrobial resistance phenotypes and their genetic basis is a priority to contribute to public health policies.